2021
DOI: 10.1371/journal.pone.0251893
|View full text |Cite
|
Sign up to set email alerts
|

Coarse woody debris decomposition assessment tool: Model development and sensitivity analysis

Abstract: Coarse woody debris (CWD) is an important component in forests, hosting a variety of organisms that have critical roles in nutrient cycling and carbon (C) storage. We developed a process-based model using literature, field observations, and expert knowledge to assess woody debris decomposition in forests and the movement of wood C into the soil and atmosphere. The sensitivity analysis was conducted against the primary ecological drivers (wood properties and ambient conditions) used as model inputs. The analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 92 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…The efficiency (E = 0.87) of model calibration for the calculated mass loss using the disks collected in situ showed that the model performance was excellent (E�0.75), and reflects a difference in model performance efficiency for model calibration against data obtained from different methods (see Discussion below). These performance metrics from model calibration step indicate that the model is applicable for assessing CWD decomposition across the range conditions on the EFs, and it is in line with design objectives [29].…”
Section: Model Calibrationmentioning
confidence: 61%
See 4 more Smart Citations
“…The efficiency (E = 0.87) of model calibration for the calculated mass loss using the disks collected in situ showed that the model performance was excellent (E�0.75), and reflects a difference in model performance efficiency for model calibration against data obtained from different methods (see Discussion below). These performance metrics from model calibration step indicate that the model is applicable for assessing CWD decomposition across the range conditions on the EFs, and it is in line with design objectives [29].…”
Section: Model Calibrationmentioning
confidence: 61%
“…The model has also been tested with respect to wood properties, including species group (hardwood and softwood), wood density (0.1 to 1.0 g cm -3 ) and size (4.0 to 45 cm in diameter). The results from the model assessment showed that CWD decomposition was highly sensitive to climatic factors, elevation, CWD properties and position (standing vs downed) [29]. Accordingly, the assessment affirms that CWDDAT should be a potentially effective tool for estimating CWD dynamics in forests.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations